2020
DOI: 10.1007/s10067-020-05199-w
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of switching from reference adalimumab to SB5 in a real-life cohort of inflammatory rheumatic joint diseases

Abstract: Objective SB5 showed comparable efficacy and safety profile in respect to adalimumab originator (ADA) in randomized clinical trials of rheumatoid arthritis (RA) and psoriasis. We aimed to describe the efficacy and safety of SB5 after switching from ADA in RA, axial spondyloarthritis (axSpA), psoriatic arthritis (PsA) and juvenile idiopathic arthritis (JIA) patients. Method Adult RA, PsA, axSpA, JIA patients treated with ADA for at least 6 months, switched to SB5 in stable clinical conditions, were eligible. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 18 publications
(26 reference statements)
2
33
0
Order By: Relevance
“…No serious TEAEs were recorded. 28 In PSO patients, Hercogová et al reported that the incidence of TEAEs, serious TEAEs, treatment discontinuations due to TEAEs, injection site reactions, and hypersensitivity reactions were comparable in the three treatment arms through to week 66. 30 Blauvelt et al did not find any relevant differences with respect 7.6%, and R-B: 9.1%).…”
Section: Safety Resultsmentioning
confidence: 99%
“…No serious TEAEs were recorded. 28 In PSO patients, Hercogová et al reported that the incidence of TEAEs, serious TEAEs, treatment discontinuations due to TEAEs, injection site reactions, and hypersensitivity reactions were comparable in the three treatment arms through to week 66. 30 Blauvelt et al did not find any relevant differences with respect 7.6%, and R-B: 9.1%).…”
Section: Safety Resultsmentioning
confidence: 99%
“…SB5 was approved by the EMA and FDA in 2017 and 2019, respectively, and was proven to have s similar structure, function, and PK to ADL (17,18). Weinblatt et al (17,19) phase III, randomized, double-blind, parallel group study comparing SB5 with ADL in efficacy, safety, and immunogenicity included 544 moderate to severe RA patients, despite MTX treatment.…”
Section: Sb5 (Imraldi/hadlima)mentioning
confidence: 99%
“… 8 , 9 Switching from ADA to SB5 was demonstrated not to impact the efficacy and immunogenic profile of RA patients, 9 and short-term real-life data confirmed efficacy and results in inflammatory bowel diseases (IBD), plaque psoriasis, PsA patients switched to SB5, as well as in mixed cohorts of iRMD. 10 12 …”
Section: Introductionmentioning
confidence: 99%